2021
DOI: 10.5114/ceji.2021.112450
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil gelatinase-associated lipocalin for predicting anemia of inflammation in children with urinary tract infection

Abstract: anemia of inflammation (ia), the second most common cause of childhood anemia, results from macrophage iron sequestration and impaired erythropoiesis. neutrophil gelatinase-associated lipocalin (nGaL) plays an important role in innate microbial immunity through its influence on intracellular iron homeostasis and inhibition of erythropoiesis. The predictive value of nGaL in ia was assessed in 74 children (age 6.30 ±3.64 ci): 1.128 (1.005-1.265), p = 0.040]. in stepwise multiple analysis age independently corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“… 26 , 27 In contrast, in another study, there was no significant difference in LCN2 levels between anemic and non-anemic subjects, and there was no significant association between LCN2 and hemoglobin levels. 28 In our study, hemoglobin levels were significantly lower in patients with elevated LCN2 levels than in those without elevated LCN2 levels. Moreover, compared with non-anemic individuals, patients with anemia had significantly higher LCN2 levels.…”
Section: Discussionsupporting
confidence: 42%
“… 26 , 27 In contrast, in another study, there was no significant difference in LCN2 levels between anemic and non-anemic subjects, and there was no significant association between LCN2 and hemoglobin levels. 28 In our study, hemoglobin levels were significantly lower in patients with elevated LCN2 levels than in those without elevated LCN2 levels. Moreover, compared with non-anemic individuals, patients with anemia had significantly higher LCN2 levels.…”
Section: Discussionsupporting
confidence: 42%
“…Subsequent studies have shown the existence of mammalian siderophores that LCN2 also binds, suggesting that LCN2 might be involved in the regulation of systemic and local iron metabolism. Consequently, several studies have shown strong association between iron metabolism, hematological indices, and LCN2 concentration [91 ▪ ,92,93]. LCN2 appears to regulate tissue-specific iron balance [94–96], and might play a pivotal role in the protection of tissue against high free iron levels.…”
Section: Lipocalin-2 At the Crossroads Of Inflammation Iron Homeostas...mentioning
confidence: 99%